Analisis Kontribusi Sektor Pertambangan, Kontribusi Sektor Pertanian, Saldo APBD, RLS, dan PAD terhadap Pertumbuhan Ekonomi dan Pembangunan Manusia di Kabupaten dan Kota di Kalimantan Selatan Tahun 2012-2021 - Aida, Nur (PPJP ULM, 2024)
The Purpose of this research is to find out the mining sector affects economic growth and effects HDI in regencies and cities in South Kalimantan. The variables in this study are the Mining Sector, Agricultural Sector, GRDP Growth, HDI, Regional Revenue, The Average Length of School, and Saldo. This study used panel data regression analysis with FEM. The results show that the Mining Sector has a positive significant effect on GRDP Growth. The Agricultural Sector and the Proportion of Budget Surplus/Deficit to the APBD have a positive not significant effect. Meanwhile, The Average Length of School has a significant negative effect on GRDP growth. The Mining sector has a significant positive effect on HDI, so there are no symptoms of resource curse. The agricultural sector and Regional Revenue have a significant positive effect on HDI. The Proportion of Budget Surplus/Deficit to the APBD has a significant negative effect on HDI.